Uji Efektivitas Antibakteri Ekstrak Metanol Kulit Batang Pohon Raru (Cotylelobium melanoxylon Pierre) Terhadap Bakteri Staphylococcus aureus, Escherichia coli - Hepni Sibagariang; Faisal Yusuf; Sherly H. Hutagaol; Lamro Manalu (Herbal Medicine Journal, 2026)
The bark of the raru tree possesses bioactive compounds with promising antibacterial properties. Compounds such as flavonoids, alkaloids, tannins, and saponins are known for their ability to suppress bacterial proliferation. This research investigates the antibacterial activity of methanolic extracts derived from raru bark against Staphylococcus aureus and Escherichia coli. A series of laboratory-based assays were conducted, employing raru bark extract (Cotylelobium melanoxylon Pierre) at concentrations of 25%, 50%, 75%, and 100%, utilizing the diffusion technique to assess its inhibitory effects. The findings indicate that a 25% concentration of raru bark extract produces an inhibition zone of 12.43 mm against Staphylococcus aureus and 13.26 mm against Escherichia coli, both reflecting a substantial antimicrobial effect. At a 50% concentration, the extract demonstrates enhanced activity, yielding inhibition zones of 16.91 mm and 17.05 mm for S. aureus and E. coli, respectively still within the strong efficacy range. Increasing the concentration to 75% further amplifies the antibacterial impact, with zone diameters reaching 20.26 mm for S. aureus and 20.00 mm for E. coli. At full strength (100% concentration), the extract exhibits pronounced antimicrobial potency, forming inhibition zones of 24.95 mm and 24.88 mm for S. aureus and E. coli, respectively, indicating a very strong antibacterial capacity.